Incident stroke among Ghanaians with hypertension and diabetes: A multicenter, prospective cohort study - Sarfo, F.S.; Mobula, L.M.; Plange-Rhule, J.; Ansong, D.; Ofori-Adjei, D. (Journal of the Neurological Sciences, 2018)
Background The burden of stroke among hypertensive and diabetic population in sub-Saharan Africa remains high. We sought to identify the risk factors associated with stroke occurrence in these high-risk population groups. Methods A prospective cohort study involving adults with hypertension and or type II diabetes mellitus at 5 public hospitals in Ghana who were stroke-free at enrollment. Patients were followed every 2 months at clinic for 18 months and assessed clinically for first ever stroke by physicians. We calculated crude incidence rates for stroke and assessed the factors associated with stroke occurrence using a multivariate Cox Proportional Hazards regression models. Results Of 3220 eligible participants with 3805 person-years of follow-up, there were 54 clinically confirmed new strokes. Incidence rate of stroke was 14.19 events per 1000 person-years [95% CI: 10.77–18.38], with rates among diabetics with hypertension being 16.64 [10.58–25.00], hypertension of 13.77 [9.33–19.64] and diabetes was 9.81 [3.59–21.74]. Two factors independently associated with stroke occurrence were previous cigarette smoking with adjusted HR (95% CI) of 2.59 (1.18–5.67) and physical inactivity, 1.81 (1.06–3.10). In secondary analysis, stage II hypertension compared with optimal BP was associated with aHR of 3.04 (1.00–9.27), p = .05 for stroke occurrence. Conclusion Incident stroke among Ghanaians with hypertension and diabetes is quite high. Stricter control of blood pressure and engaging in regular physical activities are strongly recommended to reduce the risk of strokes.
Keywords: Incident stroke; Risk factors; Prospective study; West Africa